Study the Effects of Heavy Metals (Lead and Cadmium) on Some Biochemicalparameters of Dairy Cattle in Baghdad Province - Khalid Sh. Salman; Tamara N. Dawood (Institute of Medico-legal Publications Pvt Ltd, 2021)
This study investigatesthe effects of heavy metals (Lead and Cadmium) on some biochemical parametersof dairy cattle in Baghdad province(Taji, Abu Ghraib, Al-Fudilia, Letifia and Youssoufia)regions.Thirtysamples of blood from dairy cattle in five different regions were taken to measure the Lead and Cadmiumconcentration by atomic absorptionwhile serum were collected for measuring, liver enzymes (aspartateaminotransferase AST and alanine aminotransferase ALT) activity,Serum total protein, serum albumin,serum globulin and serum creatinineconcentration.The results showed a significant increase (p< 0.05) in theleadand cadmium ion concentration in the blood sample of the dairy cowsin Youssoufia region comparedwith other region. On the other hand, the total protein and globulin concentration of the dairy cattle in AbuGhraib region recorded significantly (p < 0.05) higher value compared with Letifia region. While Albuminand creatinine concentrations showed non-significant (p > 0.05) differences among the different regions.Liver enzyme AST concentration showed significant increase (p < 0.05) in the serumof dairy cows in Letifiaand Youssoufia regions. However, serum ALT were increased significantly(p < 0.05) in Letifia than AbuGhraib region.Concluded from thisstudythatdairy cattle inLetifia and Youssoufia regions were subjected topollution with heavy metals which caused Increased heavy metal content in the blood of cattle and affecttheir health by increased the concentration of liver enzyme and reduction of total protein in the blood ofdairy cattle compared with other region in Baghdad province.